Crawling Experience Predicts Avoidance of Real Cliffs and Water Cliffs: Insights from a New Paradigm. (23rd February 2016) - Burnay, Carolina; Cordovil, Rita
Abstract : This study examined the influence of age, crawling‐onset age, and crawling experience on infants' adaptive behavior in situations that can lead to dangerous falls. Thirty‐one infants with variable amounts of crawling experience were tested in a new paradigm that used a real cliff and a water cliff, with a harness system to guarantee safety. Consistent with previous findings obtained in studies with real and visual cliffs, infants with more crawling experience were more likely to avoid the real cliff. More importantly, greater crawling experience was associated with a greater likelihood of avoiding the water cliff. The new paradigm offers exciting opportunities to study the development of adaptive behavior in risky environments.